The role of parents and communities in promoting entrepreneurial careers for vocational high school students - Timan, Agus; Maisyaroh, Maisyaroh; Benty, Djum Djum Noor; Adha, Maulana Amirul; Valdez, Anabelie Villa; Saputra, Bagus Rachmad (Institute of Advanced Engineering and Science, 2024)
An ironic situation has emerged where vocational school graduates, who are trained to be work-ready, have the highest unemployment rates. This study investigates the role of the community and students’ parents in promoting entrepreneurial careers among vocational school students in Malang, Indonesia. Using a qualitative approach, the research was conducted at three vocational high schools through in-depth interviews, observations, and documentation. Data reliability was ensured through credibility measures such as triangulation, verifying sources, and enhancing reference materials’ consistency and sufficiency. A multi-case design with constant comparative analysis was employed. The findings reveal several key roles of parents and communities in fostering entrepreneurship, namely: i) Entrepreneurship is taught theoretically and practically through business incubation, the Creative Entrepreneurship Program, and managing school business units; ii) Parents support entrepreneurship by purchasing students’ products, stocking the school canteen, collaborating in product sales, and participating in brainstorming sessions; iii) Schools partner with local micro, small and medium enterprises (MSMEs) and national and international companies to train students; and iv) The community and parents assist in marketing students’ products, and some businesses related to the school’s program serve as practice venues for students. This study contributes theoretically as a reference on the role of parents and the community in encouraging entrepreneurship in vocational schools. Practically, it serves as a guide for school administrators to involve parents and the community in school entrepreneurial activities.